2020
DOI: 10.17509/jpp.v20i3.29226
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception of Online Learning during Pandemic Covid-19

Abstract: Since March 2020, the case of coronavirus disease or known as Covid-19, has become a global pandemic. According to UNESCO, schools are closed in about 100 countries due to a public health emergency, including Indonesia. The condition forces teachers to make the transition of the way they teach from face to face learning to online learning. This study investigated EFL teachers’ Perception of online English language learning. Their perceptions were analyzed in three aspects: perceived usefulness, perceived ease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(179 citation statements)
references
References 9 publications
(13 reference statements)
9
126
1
5
Order By: Relevance
“…This may seem to contradict previous studies [13] that related high levels of professional experience to a low risk of burnout; however, taking into account that the pandemic context created new stressors, such as tech-nostress and a lack of resources and administrative support [9,65], the situation seems to have changed. Consequently, these results may be in line with the latest studies that suggested that experienced and self-confident teachers in face-to-face teaching became suddenly deskilled when transitioning to online teaching, experiencing disempowerment, vulnerability and frustration in using remote technology [72,82,83]. At the same time, openness to new technology, confidence and increased digital competences [69] could protect younger teachers from burnout symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…This may seem to contradict previous studies [13] that related high levels of professional experience to a low risk of burnout; however, taking into account that the pandemic context created new stressors, such as tech-nostress and a lack of resources and administrative support [9,65], the situation seems to have changed. Consequently, these results may be in line with the latest studies that suggested that experienced and self-confident teachers in face-to-face teaching became suddenly deskilled when transitioning to online teaching, experiencing disempowerment, vulnerability and frustration in using remote technology [72,82,83]. At the same time, openness to new technology, confidence and increased digital competences [69] could protect younger teachers from burnout symptoms.…”
Section: Discussionsupporting
confidence: 84%
“…On the beneficial side, findings showed that the usefulness and ease of online teaching platforms and learning management systems as an alternative to sustain education during times of emergency, such as with Covid-19, were regarded positively by the teachers (Rahayu & Wirza, 2020;Rifiyanti, 2020). One of the aspects that the teachers valued is that during this pandemic they adopted new roles as remote instructors and gained experience in terms of teaching online, while also increasing their technological knowledge to integrate pedagogical and content knowledge, an important component of teacher competencies (Lie et al, 2020;Moser et al, 2021).…”
Section: Findings Of the Third Research Question Based On The Attitudes And Motivations Of Teachers And Students Towards Emergency Onlinementioning
confidence: 99%
“…Although teachers tried hard to provide productive online teaching by engaging students in learning to increase their competence and to find new alternatives in their teaching sessions, they did not agree on the effectiveness of emergency online teaching. Among the reasons for teachers and students' negative attitudes are lack of prior experience and knowledge in online teaching or learning and lack of affinity with technology, particularly in the case of older teachers (Aji et al, 2020;Astuti & Solikhah, 2021;Fuad et al, 2020;Lie et al, 2020;Moser et al, 2021;Novikov, 2020;Rahayu & Wirza, 2020). It was found that although the students were ready to adapt to emergency remote learning, the unvaried and monotonous online learning environment (Fuad et al, 2020) made face-to-face learning more favourable for students (Patricia Aguilera-Hermida, 2020;Zboun & Farrah, 2021).…”
Section: Findings Of the Third Research Question Based On The Attitudes And Motivations Of Teachers And Students Towards Emergency Onlinementioning
confidence: 99%
“…Some of the teachers are unable to access information from internet, use various learning applications, and make media for lesson video [9]. [10] through their study on Strategies and Problems Faced by Indonesian Teachers in Conducting E-Learning System During COVID-19 Outbreak found that some of the teachers were categorized as an old teacher. It also affects their effort and ability in struggling with elearning technology.…”
Section: Teacher's Ability To Use Digital Technologymentioning
confidence: 99%